On the way to the institute of urban studies in Ukraine: contribution of e-magazine «City: history, culture, society» - Zhmaka, Vitaliy (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2021)
На шляху до інституалізації урбаністичних студій в Україні: внесок е-журналу «Місто: історія, культура, суспільство»